The Effectiveness of Adolescent Reproductive Health Education (KRR) Case Base Learning (CBL) Method on Risky Sexual Behavior of Adolescents Based on the Health Belief Model In Ngebong Village, Pakel District Tulungagung Regency - Eko Winarti; M. Ali Sodik; Sentot Imam Suprapto (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2023)
The risk of sexual behavior in adolescents is still a problem in Indonesia, causing the high number of pregnancies aged 15-19 years to reach 47 per 100 pregnancies, with one in nine girls marrying early in Indonesia. The purpose of this study is to determine the effectiveness of the adolescent reproductive health education case-based learning (CBL) method on adolescent risk sexual behavior based on the Health Belief Model (HBM) at Ngebong, Pakel, Tulungagung in 2022.This study uses an quasy experimental approach. The sample of 60 respondents was divided into 30 intervention group respondents and 30 control group respondents. The data collection instrument uses questionnaires that have been tested for validity and reliability. Data analysis using the Mann-Whitney test.The results showed that the CBL method of health education has proven effective in increasing perceived susceptibility, perceived severity, perceived benefits, and perceived self-efficacy and reducing perceived barriers and risk sexual behaviors in adolescents at Ngebong, Pakel, Tulungagung in 2022.These findings demonstrate the importance of the CBL method of adolescent reproductive health education to the reduction of risk sexual behavior in adolescents. This research has implications for improving healthy adolescent sexual behavior so that adolescents can become productive and accomplished adolescents.